Generalizing schemes at the preparatory faculty - Sira, L.; Сіра, Лариса Іванівна (Rome : Potere della ragione, 2020)
The most important feature of present-day education is the variety of methods and ability to organize it simultaneously at different complexity levels. Its well-known that international students usually do not like learning long, not always logically constructed and often incomprehensible rules. They find it difficult to relate the rule from the textbook to a specific example. So they are willing to study the material presented in the form of logic diagrams, where the main components are highlighted, and at first glance you can find important items. Besides, working on the materials according to the scheme, the student not only retells its content, but makes construction of his answer. As a result, students' thinking and coherent speech is developing.
Keywords: методика